2020
DOI: 10.3390/catal10121405
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Multiscale Process Modeling of Ethane, Propane and Butane Dehydrogenation Reactions: A Review

Abstract: Olefins are among the most important structural building blocks for a plethora of chemical reaction products, including petrochemicals, biomaterials and pharmaceuticals. An ever-increasing economic demand has urged scientists, engineers and industry to develop novel technical methods for the dehydrogenation of parent alkane molecules. In particular, the catalysis over precious metal or metal oxide catalysts has been put forward as an alternative way route to thermal-, steam- and fluid catalytic cracking (FCC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 67 publications
(122 reference statements)
1
15
0
1
Order By: Relevance
“…The DH of propane and butane on Cr 2 O 3 (0001) has also been investigated by 1p-KMC simulations. [253][254][255] Chromiun oxide catalysts are used in the so-called CATOFIN process for the production of olefins, such as propylene (from propane) and iso-butylene (from iso-butane). 255 Such studies have delivered insights into the most abundant products of the reaction pathways investigated, unwanted pathways leading to side-products or poisons, and the nature of catalyst deactivation by coking.…”
Section: B the Complexity Of Chemical Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The DH of propane and butane on Cr 2 O 3 (0001) has also been investigated by 1p-KMC simulations. [253][254][255] Chromiun oxide catalysts are used in the so-called CATOFIN process for the production of olefins, such as propylene (from propane) and iso-butylene (from iso-butane). 255 Such studies have delivered insights into the most abundant products of the reaction pathways investigated, unwanted pathways leading to side-products or poisons, and the nature of catalyst deactivation by coking.…”
Section: B the Complexity Of Chemical Pathwaysmentioning
confidence: 99%
“…[253][254][255] Chromiun oxide catalysts are used in the so-called CATOFIN process for the production of olefins, such as propylene (from propane) and iso-butylene (from iso-butane). 255 Such studies have delivered insights into the most abundant products of the reaction pathways investigated, unwanted pathways leading to side-products or poisons, and the nature of catalyst deactivation by coking. In the case of DH of propane on Cr 2 O 3 (0001), 254 it was found that the accumulation of propylene and propyne in the reaction mixture adversely affects the reaction rate and selectivity.…”
Section: B the Complexity Of Chemical Pathwaysmentioning
confidence: 99%
“…Ethylene is a necessary chemical raw material, and ethane dehydrogenation is one of the essential methods to produce ethylene. Though there is comprehensive application in industry, there are still numerous challenges [76], such as deactivation of the catalyst. The study of the ethane dehydrogenation mechanism and the funding of more effective catalysts will be helpful to confront these challenges.…”
Section: Dehydrogenation and Hydrogenationmentioning
confidence: 99%
“…Ethylene is a necessary chemical raw material, and ethane dehydrogenation the essential methods to produce ethylene. Though there is comprehensive applic industry, there are still numerous challenges [76], such as deactivation of the catal study of the ethane dehydrogenation mechanism and the funding of more effect lysts will be helpful to confront these challenges. Using density functional theory initio microkinetic model, Jalid et al [77] systematically investigated the reaction nism of ethane dehydrogenation with transition metals (Pt, Pd, Co, Ni, Rh, Ru, Au, and Ag) as catalysts and CO2 as mild oxidant.…”
Section: Dehydrogenation and Hydrogenationmentioning
confidence: 99%
“…Furthermore, cycloalkanes are commonly used industrial chemicals which have realized long-distance transportation and large-scale storage in the chemical industry. However, the release of hydrogen in cycloalkanes is difficult because of the high thermodynamic limitation in C-H bond cleavage [5,[12][13][14]. Extensive studies found that cycloalkane dehydrogenation with heterogeneous catalysts should be carried out in gas-phase at high temperature (above 300 • C) to obtain a high hydrogen production rate and cycloalkane conversion [11].…”
Section: Introductionmentioning
confidence: 99%